Photochromism in the bi-imidazolyl system - Litobarsky, M.W. (1973)
The work, which is reported in this thesis, is concerned with the photochromic processes, or light induced changes of colour displayed by the hexaaryl bi-imidazolyl system. The thesis includes a study of the solid state photochromic decay reaction, in which the colour change is brougnt about by the dimerisation of triphenyl imidazolyl radicals. Equipment, used in conjunction with a U. V. /visible spectrophotometer, was assembled to allow the process to be followed at various temperatures and from the data accrued a kinetic scheme, based upon a diffusion controlled reaction involving a radical-dinier complex species, has been suggested. Investigations were also carried out into. the photochromic processes of the bi-imidazolyl system in benzene solution. Based on earlier observations, the work included the study of the effect of variation of the parent dimer concentration upon the generation and decay kinetics of the triphenyl imidazolyl radicals and the related radicals fluorinated on the 2 phenyl ring. Kinetic schemes, most of which have necessarily involved a postulation of radical-dimer complexes of some sort, have been formulated for each radical system at each dimer concentration used. Rate constants for the reactions have been given. The electron spin resonance spectra for the three fluorinated derivatives of the triphenyl imidazolyl radical have been reported. Assignment of the splitting constants was attempted by use of simple Hückel molecular orbital calculations but this proved largely unsuccessful. Accurate theoretical reproduction of the experimental spectra was thus not achieved. It was decided, that Hückel was in too many ways unsatisfactory for the system, and work on an alternative, more complete molecular orbital approach (that of Pople, Pariser and Parr) was initiated. A computer program was obtained to permit such calculations to be made, and although not all problems had been overcome by the end of the time allowed for this thesis much headway had been made, and guide lines for further work have been suggested.